Attempts to Enhance The Learning Outcomes of Students by The Use of Image-Based Student Worksheets on Nervous System Materials - Lusiana Yosanda Sari; Soesy Asiah Soesilawaty; Rr Marhamah (CV. Dharma Samakta Edukhatulistiwa, 2023)
The problem with this study is that the biological learning outcomes of SMA Lab School UPI students in class XI IPA 1 remain low. The objective of this study is to enhance the biology learning outcomes of students by utilizing image-based worksheets. The researcher conducted classroom action research in two cycles in order to accomplish this goal. This study involves collaborative action research in the classroom that makes use of the Kemmis and Taggart methodology. Students in class XI IPA 1 at SMA Lab School UPI served as the research subjects. Tests, surveys, and observations are the approaches used in this study to collect data. An observation sheet serves as the research tool, and it is assessed qualitatively. Additionally, the concept mastery test results, which are analyzed quantitatively, are supplied. The study's findings indicate that, when image-based student worksheets were used, biology learning outcomes in the nervous system of the classroom were improved, with 19% of students reaching the minimum completeness limit score. Similarly, in cycle I, the average result of the concept mastery test was 77, and 61% of students met the minimum completeness limit score. The average concept mastery score increased to 85 in Cycle II, and a greater proportion of students met the 92% minimum completion criteria.